Advances in Group Processes - Lawler, Edward J. (Advances in Group Processes Ser., 2020)
Volume 37 brings together papers related to a variety of topics in small groups and organizational research. The volume includes papers that address theoretical and empirical issues related to consumer social privilege, group processes and disrupted environments, the use of time as a construct and the affective bases of self.